Histomorphometric Study of the Proportion of Different Zones of Adrenal Cortex A Postmortem Study - Siddiqua, Dilruba; Nurunnabi, Abu Sadat Mohammad; Johora, Fatema; Hena, Hasna; Shahriah, Sunjida; Ara, Shamim (Journal of Bangladesh Society of Physiologist, 2015)
Background: The human adrenal cortex shows a distinct proportion of three zones, named zona glomerulosa, zona fasciculate & zona reticularis, from outer inwards, in its histological appearance with differences in its cellular components and functions. Objective: The aim of the present study was to see the variation in the proportion of zones of the adrenal cortex in different age-group in a Bangladeshi population. Methods: This cross-sectional, descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2008 to June 2009, based on collection of 140 post mortem human adrenal glands from 70 unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into four age-groups including A (11-20 years), B (21-30 years), C (31-40 years) & D (41-60 years). Histological slides were prepared by using routine haematoxylin and eosin stain (H & E). Five best prepared slides from each group were examined under light compound microscope with low magnification. The thickness of different layers adrenal cortex were measured by using ocular and stage micrometer and then converted into percentage volume. Results: The mean volume of the zona glomerulosa, zona fasciculata and zona reticularis of the right adrenal cortex were found 14.16±0.79%, 78.40±1.14%, 7.44±0.52% in group A; 14.58±0.38%, 78.00±0.71%, 7.42±0.38% in group B; 14.34±0.83%, 78.56±0.52%, 7.30±0.50% in group C; 14.08±1.23%, 78.80±1.10%, 7.10±0.22% in group D respectively. The mean volume of the zona glomerulosa, zona fasciculata and zona reticularis of the left adrenal cortex were found 14.66±0.34%, 78.84±0.82%, 7.72±0.48% in group A; 14.62±0.30%, 78.54±0.84%, 7.58±0.43% in group B; 14.90±0.96%, 79.20±0.45%, 7.34±0.42% in group C; 14.70±1.25%, 79.40±0.55%, 7.30±0.35% in group D respectively. Conclusion: No difference was found statistically significant in the percentage volume of the three zones of the adrenal cortex with advancing age in Bangladeshi people. DOI: http://dx.doi.org/10.3329/jbsp.v9i2.22803 Bangladesh Soc Physiol. 2014, December; 9(2): 89-93